Strategy Formulation and Implementation in Indonesian Public Hospitals: A Multiple Case Study - Sinta Sinta; Siswani Siswani; Restika Osin Sukur; Reza Hapid; Mira Veranita (International Journal of Business, Management and Economics, 2026)
Effective strategy formulation and implementation remain among the most persistent challenges confronting public hospital management in developing country contexts, where institutional complexity, resource constraints, and regulatory turbulence shape organizational decision-making in distinctive ways. This study employs a qualitative multiple case study design to investigate how public hospitals in West Java Province, Indonesia, formulate and implement organizational strategies, and what factors mediate the gap between strategic intent and operational reality. Data were collected from three Type B public hospitals, referred to pseudonymously as RS A, RS B, and RS C, through 30 in-depth interviews with hospital directors, strategic planning managers, department heads, and frontline staff, supplemented by document analysis of hospital strategic plans (RENSTRA), performance reports, and board meeting minutes over a six-month field period. Thematic analysis following Braun and Clarke (2006) identified four overarching themes: (1) the politics and processes of strategy formulation, (2) the strategy-structure alignment challenge, (3) human resource and leadership factors in strategy implementation, and (4) performance monitoring and adaptive strategy. Findings reveal that strategy formulation in Indonesian public hospitals is characterized by isomorphic compliance pressures that constrain genuine strategic choice, while implementation is critically shaped by middle management capacity, organizational culture, and the coherence of performance management systems. The study contributes a contextually grounded theoretical framework for understanding strategy processes in public health organizations and offers practical implications for hospital governance reform